MidCog study: a prospective, observational cohort study investigating health literacy, self-management skills and cognitive function in middle-aged adults. Issue 2 (23rd February 2023) - Kim, Minjee; Kwasny, Mary J; Bailey, Stacy C; Benavente, Julia Y; Zheng, Pauline; Bonham, Morgan; Luu, Han Q; Cecil, Patrick; Agyare, Prophecy; O'Conor, Rachel; Curtis, Laura M; Hur, Scott; et al.
Abstract : Introduction: The lack of definitive means to prevent or treat cognitive impairment or dementia is driving intense efforts to identify causal mechanisms. Recent evidence suggests clinically meaningful declines in cognition might present as early as middle age. Studying cognitive changes in middle adulthood could elucidate modifiable factors affecting later cognitive and health outcomes, yet few cognitive ageing studies include this age group. The purpose of the MidCog study is to begin investigations of less-studied and potentially modifiable midlife determinants of later life cognitive outcomes. Methods and analysis: MidCog is a prospective cohort study of adults ages 35–64, with two in-person interviews 2.5 years apart. Data will be collected from interviews, electronic health records and pharmacy fill data. Measurements will include health literacy, self-management skills, cognitive function, lifestyle and health behaviours, healthcare use, health status and chronic disease outcomes. Associations of health literacy and self-management skills with health behaviours and cognitive/health outcomes will be examined in a series of regression models, and moderating effects of modifiable psychosocial factors. Finally, MidCog data will be linked to an ongoing, parallel cohort study of older adults recruited at ages 55–74 in 2008 ('LitCog'; ages 70–90 in 2023), to explore associations between age, health literacy, self-management skills, chronic diseases, health status and cognitive function among adults ages 35–90. Ethics and dissemination: The Institutional Review Board at Northwestern University has approved the MidCog study protocol (STU00214736). Results will be published in peer-reviewed journals and summaries will be provided to the funders of the study as well as patients.